Cross-Talks between Natural Killer Cells and Distinct Subsets of Dendritic Cells - Ferlazzo, Guido; Morandi, Barbara (Frontiers in Immunology, 2014)
In recent years, the essential role of bidirectional cross-talk between natural killer (NK) and dendritic cells (DC) during immune responses has been clearly elucidated. In particular, this cross-talk results in the development of an efficient innate response, through DC-mediated NK cell activation, and a potent adaptive immune response, through NK-mediate DC editing and maturation. Recently, some novel human DC subsets have been identified: migratory DCs in afferent lymph and draining lymph nodes; CLEC9A+/ BDCA3+ DCs in interstitial dermis, liver, lung; inflammatory DCs in several fluids secondary to flogosis. At the same time, it has been shown that also human NK cells are present in these compartments. Here we will review the most recent findings on NK/DC cross-talk and we will discuss the necessity of acquiring more complete knowledge about these interactions in view of the new information available on both DC and NK cell subsets.